Navigating cardiac arrest together: A survivor and family-led co-design study of family needs and care touchpoints - Matthew J. Douma; Samina Ali; Tim A.D. Graham; Allison Bone; Sheila D. Early; Calah Myhre; Kim Ruether; Katherine E. Smith; Kristin Flanary; Thilo Kroll; Kate Frazer; Peter G. Brindley (Resuscitation Plus)
Introduction: This study aimed to i) identify the care needs of families experiencing cardiac arrest; and ii) co-identify strategies for meeting the identified care needs. Cardiac arrest survivors and family members (of survivors and non-survivors) were engaged as “experience experts,” collaborators and co-researchers in this study. Methods: A qualitative study using semi-structured interviews of cardiac arrest survivors and family members was conducted. Participants were recruited from the membership of the Family Centred Cardiac Arrest Care Project. Interviews were recorded, transcribed, and analysed using Framework analysis. Results: Twenty-eight participants described 22 unique cardiac arrest events. We identified five primary care need themes: 1) “Help us help our loved one”; 2) “Work with us as a cohesive team”; 3) “See us: treat us with humanity and dignity”; 4) “Address our family’s ongoing emergency”; and 5) “Help us to heal after the cardiac arrest” as well as 29 subordinate care need themes. We performed touchpoint mapping to identify key moments of interaction between patients and families, and the health system to highlight potential areas for improvement, as well as strategies for meeting family care needs. Conclusion: Our participants identified varied family care needs during and long after cardiac arrest. Fortunately, many proposed strategies are inexpensive and have low barriers to adoption. However, some unmet care needs identified suggest larger systemic issues such as service gaps that leave families feeling abandoned and isolated. Overall, our findings suggest that care during and after cardiac arrest are critical components of a comprehensive cardiac arrest care system.